Consumer rationalization in the Sunnah of the Prophet: An objective study - Alzahran, Mohamed Zaher (Journal of Islamic Sciences, 2024)
This research studies an important economic topic, explains its meaning, then presents the most important prophetic hadiths mentioned in this regard, and explains their guidance, economic controls, and how to benefit from these concepts at the present time economically and legally. The main objective of the research is to study the concept of rationalizing consumption as mentioned in the Sunnah, with an explanation of its meanings and importance, with a review of a number of relevant prophetic hadiths, then explaining how to apply these concepts in the contemporary economic and legal context, with the study relying on the inductive and descriptive approach. The prophetic texts related to the topic were collected and analyzed in the legal and economic fields. The main research topics are: defining rationalization of consumption and its meaning in the Sunnah, then the prophetic hadiths that warn against extravagance and encourage moderation, and then: the economic and legal controls for rationalizing consumption and its effects. The research concluded with several results, the most important of which are: that extravagance and waste lead to economic, social and environmental problems, and emphasizing rationalization of consumption enhances financial balance at the individual and societal levels, with the citation of some prophetic hadiths that provide practical guidance to reduce waste and achieve sustainable development.